2019
DOI: 10.2147/lctt.s192643
|View full text |Cite
|
Sign up to set email alerts
|

<p>Landscape on CT screening for lung cancer in Asia</p>

Abstract: Lung cancer remains the leading cause of cancer incidence and mortality worldwide. Approximately 60% of the world’s new cases of lung cancer and deaths from it are expected in Asia in 2018. Currently, lung cancer screening using low-dose computed tomography (LDCT) is recommended for heavy smokers in North America, Europe and some countries in Asia. Tobacco smoking being the major risk factor for lung cancer, but in Asia, lung cancer in never-smokers (LCINS) is also a concern. This paper reviews on lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 69 publications
(131 reference statements)
2
18
1
2
Order By: Relevance
“…This study, on a large hospital-based cohort of individuals who underwent LDCT for lung cancer screening in South Korea, assessed the characteristics and outcomes of centrally-located lung cancer in comparison with peripherally-located lung cancer with a focus on screendetection status. The cohort of asymptomatic participants who voluntarily underwent LDCT screening enabled the evaluation of a large number of never-smokers and relatively young individuals, and reflects the real-world state of LDCT screening in East Asia, where it is widely applied to these populations (15,31). In accordance to a prior study evaluating LDCT screening in the Asian population, our data also revealed better outcomes in diagnosed stage and mortality in the screen-detected cancer group (32).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study, on a large hospital-based cohort of individuals who underwent LDCT for lung cancer screening in South Korea, assessed the characteristics and outcomes of centrally-located lung cancer in comparison with peripherally-located lung cancer with a focus on screendetection status. The cohort of asymptomatic participants who voluntarily underwent LDCT screening enabled the evaluation of a large number of never-smokers and relatively young individuals, and reflects the real-world state of LDCT screening in East Asia, where it is widely applied to these populations (15,31). In accordance to a prior study evaluating LDCT screening in the Asian population, our data also revealed better outcomes in diagnosed stage and mortality in the screen-detected cancer group (32).…”
Section: Discussionsupporting
confidence: 85%
“…However, many other regions do not yet have criteria for such screening, and emerging data suggest that expending the screening criteria would be beneficial (7,8). In East Asia, where the burden of lung cancer among never-smokers is relatively high and increasing (9)(10)(11), LDCT screening has shown promising results of mortality benefits and stage shifts in several realworld cohort studies including never-smokers (12,13), and is widely applied for both never-and ever-smokers as well as for relatively young individuals (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…8 In an ongoing study (NCT03909620) evaluating the role of LDCT for lung cancer screening at a tertiary care center in India (n ¼ 221), 33.5% of the subjects had a positive result after the first round of screening and 1.8% were diagnosed as having lung cancer (unpublished data), which is comparable with data from other countries in the region. 9 Encouragingly, the presence of radiological sequelae of tuberculosis was not associated with a positive LDCT scan in this study.…”
Section: Screening and Early Detectionmentioning
confidence: 40%
“…Third, as described in Table 1 , our patients consisted of more of limited-stage SCLC and were treated with all types of modalities compared to the previous population-based study 17 . We contend that the expanded concept of lung cancer screening may have resulted in increased numbers of lung cancer patients detected at earlier stages or with treatable disease 39 . Also, drastic improvements in treatments such as immunotherapy in the last decade may have increased the number of patients indicated for treatment 40 .…”
Section: Discussionmentioning
confidence: 99%